2016
DOI: 10.1186/s12904-016-0150-3
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes I’ve gone home feeling that my voice hasn’t been heard”: a focus group study exploring the views and experiences of health care assistants when caring for dying residents

Abstract: BackgroundIn most developed countries, Health Care Assistants comprise a significant, and growing, proportion of the residential aged care workforce. Despite the fact that they provide the majority of direct care for residents, little is known about a key care aspect of their work, namely their experience of caring for dying residents.MethodsTwenty-six Health Care Assistants working in aged residential care facilities in Auckland, New Zealand participated in six focus group discussions. Focus groups were desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 51 publications
4
65
0
Order By: Relevance
“…ANs expected that the RNs would step forward and take more responsibility when a situation became complicated. The feeling of isolation and the importance of multidisciplinary teamwork in palliative care for the older people has been described in other studies (Fryer, Bellamy, Morgan, & Gott, 2016;Phillips, Davidson, Jackson, & Kristjanson, 2008). The team is not only supportive in situations relating to the care of an individual patient but also acts as a body for learning and education.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…ANs expected that the RNs would step forward and take more responsibility when a situation became complicated. The feeling of isolation and the importance of multidisciplinary teamwork in palliative care for the older people has been described in other studies (Fryer, Bellamy, Morgan, & Gott, 2016;Phillips, Davidson, Jackson, & Kristjanson, 2008). The team is not only supportive in situations relating to the care of an individual patient but also acts as a body for learning and education.…”
Section: Discussionmentioning
confidence: 91%
“…It is obvious that managers of RCFs must foster a more collaborative and team-based work environment to improve the quality of palliative care. Many studies have highlighted the importance of teamwork in palliative care (Finucane, Stevenson, Moyes, Oxenham, & Murray, 2013;Fryer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Karlsson, Ekman & Fagerberg (2008) presented the point of view of nursing assistants as expecting the registered nurses to be equal team members but that the registered nurses had the main responsibility for the care of older people living in nursing homes. It has also been identified that nursing assistants can feel that their awareness and experience were not appreciated by other team members when taking care of older people who were dying (Fryer, Bellamy, Morgan, & Gott, 2016).…”
Section: Nursing Staff In Nursing Homesmentioning
confidence: 99%
“…Another problem with taking care of older people at the end of life seen in a study by Österlind et al (2011) was that nursing assistants in nursing homes did not speak very much about death and dying with the older people because of their own fear of death (Österlind et al, 2011). One possible reason for this, as described by Fryer et al, is that education about palliative and end-of-life care has been recognized as lacking by many nursing assistants (Fryer et al, 2016;Goddard, Stewart, Thompson, & Hall, 2013). The nursing staff wanted end-of-life care education, and identified that they needed more knowledge to be able to give appropriate end-of-life care (Goddard et al, 2013).…”
Section: Nursing Staff In Nursing Homesmentioning
confidence: 99%
“…With an increasing aging population, particularly in the oldest old category (i.e., age 85 and older), endof-life (EOL) care within nursing communities has become a common practice, and by 2020, 40% of residents ages 65 and older are predicted to die in nursing facilities (Tilden, Th ompson, Gajewski, & Bott, 2012). CNAs' involvement with residents also means CNAs play a critical role in the provision of chronic and EOL care (Fryer, Bellamy, Morgan, & Gott, 2016). Although being a CNA is a physically and emotionally challenging job, CNAs possess a strong desire to provide compassionate, effective EOL care, despite often lacking confi dence and knowledge in pain management and comfort measures (Ersek, Kraybill, & Hansberry, 1999).…”
mentioning
confidence: 99%